Composite g-C3N4/NiCo2O4 with Excellent Electrochemical Impedance as an Electrode for Supercapacitors. (5th December 2022) - Cui, Danfeng; Fan, Zheng; Fan, Yanyun; Chen, Hongmei; Li, Penglu; Duan, Xiaoya; Yan, Shubin; Xu, Hongyan; Xue, Chenyang
Abstract : For the development of supercapacitors, electrode materials with the advantages of simple synthesis and high specific capacitance are one of the very important factors. Herein, we synthesized g-C3 N4 and NiCo2 O4 by thermal polymerization method and hydrothermal method, respectively, and finally synthesized NiCo2 O4 /g-C3 N4 nanomaterials by mixing, grinding, and calcining g-C3 N4 and NiCo2 O4 . NiCo2 O4 /g-C3 N4 nanomaterials are characterized by X-ray diffraction and X-ray photoelectron spectroscopy. The microscopic morphology, lattice structure, and element distribution of NiCo2 O4 /g-C3 N4 nanomaterials were characterized by scanning electron microscopy (SEM), transmission electron microscopy, high resoultion transmission electron microscopy, and mapping methods. The electrochemical performance and cycle stability of NiCo2 O4 /g-C3 N4 were tested in a 6 M KOH aqueous solution as electrolyte under a three-electrode system. Due to the physical mixing structure of g-C3 N4 and NiCo2 O4 nanomaterials, the electrochemical energy storage performance of NiCo2 O4 /g-C3 N4 supercapacitor electrodes is better than that of NiCo2 O4 supercapacitor electrodes. At a current density of 1 A/g, the capacitances of NiCo2 O4 and NiCo2 O4 /g-C3 N4 are 98.86 and 1, 127.71 F/g, respectively. At a current density of 10 A/g, the capacitance of NiCo2 O4 /g-C3 N4 supercapacitor electrode maintains 70.5% after 3, 000 cycles. NiCo2 O4 /g-C3 N4 electrode has excellent electrochemical performance, which may be due to the formation of physical mixing between NiCo2 O4 and g-C3 N4, which has broad application prospects. This research is of great importance for the development of materials in high-performance energy storage devices, catalysis, sensors, and other applications.